Peer production, the commons, and the future of the firm - Benkler, Yochai (Strategic organization, 2017)
From free and open source software, through Wikipedia to video journalism, peer production plays a more significant role in the information production environment than was theoretically admissible by any economic model of motivation and organization that prevailed at the turn of the millennium. Its sustained success for a quarter of a century forces us to reevaluate three core assumptions of the standard models of innovation and production. First, it places intrinsic and social motivations, rather than material incentives, at the core of innovation, and hence growth. Second, it challenges the centrality of property, as opposed to the interaction of property and commons, to growth. And third, it questions the continued centrality of firms to the innovation process.